Mechanosynthesis of a Structurally Characterized, Well‐Defined Graphitic Phosphorus‐Linked Carbon Nitride (g‐PCN) with Water Splitting Activity - Blaine G. Fiss; Georgia Douglas; Michael Ferguson; Jorge Becerra; Jesus Valdez; Trong‐On Do; Tomislav Friščić; Audrey Moores (Advanced Materials Interfaces)
Abstract Graphitic phosphorus‐linked triazine networks (g‐PCNs) are an emergent class of carbon nitride materials that have attracted attention for their potential role in developing metal‐free water splitting photocatalysts, but remain difficult to access due to complicated synthetic procedures based on long reaction times, high‐temperature annealing (above 500 °C), and poor structural understanding. Here, a mild, lower temperature approach for the synthesis of catalytically active g‐PCN through combining a room‐temperature mechanochemical reaction of sodium phosphide and cyanuric chloride with only 1 h annealing at 300 °C is presented. Notably, this mechanosynthesized material is sufficiently ordered to permit unprecedented structural characterization of a g‐PCN layered solid by combining solid‐state magic angle spinning, nuclear magnetic resonance spectroscopy, X‐ray photoelectron spectroscopy, powder X‐ray diffraction (PXRD), and transmission electron microscopy, supported by dispersion‐corrected density functional theory modeling. The excellent match of experimental 31P MAS NMR and PXRD data with modeling of the structure based on phosphorus‐linked triazine network layers makes the herein described mechanochemically synthesized material the first example of a photocatalytically active, as well as structurally characterized, g‐PCN.